Characteristics of Metal Enhanced Evanescent-Wave Microcavities - Takashi Wakamatsu (Sensors, 2010)
This article presents the concept of storing optical energy using a metallic air gap microcavity. Evanescent waves are stored in the air gap of a dielectric/metal/air gap/metal planar microcavity. For an air gap with a micron scale distance between the two metals, incident light excites the optical interface modes on the two metal-air interfaces simultaneously, being accompanied by enhanced evanescent fields. Numerical simulations show that the reflected light depends remarkably upon distributions of the enhanced electric fields in the air-gap at the optical mode excitations. The metallic microcavities have a Q value on the order of 102, as determined from calculations. Experimentally, a small mechanical variation of the air-gap distance exhibited a change of reflectivity.